Concealing the taste of the Guinness World's most bitter substance by using a synthetic nanocontainer. Issue 30 (20th July 2017) - Yang, Xue; Li, Shengke; Zhang, Qing-Wen; Zheng, Ying; Bardelang, David; Wang, Lian-Hui; Wang, Ruibing
Abstract : The bitterness of the world's bitterest substance was dramatically concealed by using a synthetic nanocontainer, demonstrating its significant taste-masking potential. Abstract : Upon supramolecular encapsulation by using a synthetic nanocontainer (cucurbit[7]uril), the taste of the Guinness World's most bitter substance, denatonium benzoate, was dramatically concealed during a two-bottle preference drinking test in a mammalian model, demonstrating the significant potential of cucurbit[7]uril as a taste-masking nanocontainer for the first time.